2013
DOI: 10.5301/urologia.5000035
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of massive funicular lipoma

Abstract: Intrascrotal lipomas are benign diseases that originate from adipose tissue inside the scrotal sac or constituting the scrotal wall itself. Paratesticular spermatic cord lipomas are a rare type of intrascrotal lipomas. A 78 years old patient in good health comes to our attention for massive tense-elastic swelling of left hemiscrotum appeared about 3 years ago and slowly increasing. Ultrasound evaluation of the intrascrotal mass showed inhomogeneous images mainly hyperechoic, not infiltrating the ipsilateral te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Yamamichi et al [ 13 ] reported a case of scrotal lipoma with a maximum diameter of 14 cm combined with liposarcoma (weight 250 g). The lesion described in the current report is the heaviest bilateral scrotal lipoma in the English-language literature[ 10 - 12 ], which was 995 g in weight (Figure 1D ).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Yamamichi et al [ 13 ] reported a case of scrotal lipoma with a maximum diameter of 14 cm combined with liposarcoma (weight 250 g). The lesion described in the current report is the heaviest bilateral scrotal lipoma in the English-language literature[ 10 - 12 ], which was 995 g in weight (Figure 1D ).…”
Section: Discussionmentioning
confidence: 73%
“…Large scrotal lipomas often present with scrotal enlargement and discomfort[ 10 - 12 ]. A large right scrotal mass that weighed 1100 g was reported[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary scrotal lipoma usually originates from spermatic cord. However, it can also originate outside the spermatic cord or in subcutaneous tissue [1][2][3]. We present an extremely rare case of primary scrotal lipoma which originated from subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…There is a wide range of differential diagnosis that spans from malignant to benign conditions [1,2]. The most common differentials include testicular torsion, epididymitis, varicocele, hydrocele, inguinal-scrotal hernia, epididymal cyst and testicular cancer [3,4]. Primary scrotal lipoma is a rare urological entity which usually poses a diagnostic quandary.…”
Section: Introductionmentioning
confidence: 99%
“…Lipomas are common benign mesenchymal tumours that may occur in any part of the body. These neoplasms, however, are rarely seen in the scrotum (1). In most cases, scrotal lipomas originate from the adipose tissue of the spermatic cord evolving towards the scrotum or develop in the spermatic cord itself.…”
Section: Introductionmentioning
confidence: 99%